2016
DOI: 10.3390/ijms17101742
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of JNK/NFκB Signaling Pathways in the Lipopolysaccharide-Induced Modulation of Aquaglyceroporin Expression in 3T3-L1 Cells Differentiated into Adipocytes

Abstract: Aquaglyceroporins, belonging to the family of aquaporins (AQPs), are integral plasma membrane proteins permeable to water and glycerol that have emerged as key players in obesity. The aim of this study was to investigate the expression profile of AQPs in undifferentiated and differentiated 3T3-L1 cells and to investigate the changes in expression of aquaglyceroporins in 3T3-L1 cells differentiated into adipocytes and subjected to lipopolysaccharide (LPS) mimicking inflammation occurring during obesity. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 62 publications
(114 reference statements)
1
28
0
Order By: Relevance
“…were also decreased, indicating that the silencing of AQP3 inhibits the adipogenic differentiation of porcine intramuscular preadipocytes from the overall gene expression level. A previous study has also shown that AQP3 is more permeable to glycerol compared with water [14], and AQP3 was increased in LPS-induced adipogenesis [32] and triglyceride sedimentation [37]. A combination of our and others' work supports a pivotal role of AQP3 in lipid accumulation in adipocytes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…were also decreased, indicating that the silencing of AQP3 inhibits the adipogenic differentiation of porcine intramuscular preadipocytes from the overall gene expression level. A previous study has also shown that AQP3 is more permeable to glycerol compared with water [14], and AQP3 was increased in LPS-induced adipogenesis [32] and triglyceride sedimentation [37]. A combination of our and others' work supports a pivotal role of AQP3 in lipid accumulation in adipocytes.…”
Section: Discussionsupporting
confidence: 87%
“…However, mRNAs and proteins of AQP3 were later detected in human stroma vascular fraction of omental, subcutaneous adipocyte tissue, and also in freshly isolated adipocytes [6]. Additionally, the expression of AQP3 was confirmed in murine 3T3-L1 cell line [32,33]. The inconsistent reports might be due to the relatively lower expression levels of AQP3 in mature adipose tissues [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, glycerol secretion could not be completely abolished in AQP7-deficient adipocytes [ 23 , 25 ]. While AQP7 was considered to be the sole aquaglyceroporin expressed in adipose tissue [ 26 , 27 ]—expression of AQP3, AQP9 and AQP10 and AQP3 and AQP9 has since been detected in human adipose tissue [ 28 , 29 , 30 ] and in 3T3-L1 adipocytes [ 31 ], respectively. Moreover, AQP3 mRNA levels are higher in 3T3-L1 adipocytes as compared to preadipocytes, while AQP9 mRNA levels are similar [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…While AQP7 was considered to be the sole aquaglyceroporin expressed in adipose tissue [ 26 , 27 ]—expression of AQP3, AQP9 and AQP10 and AQP3 and AQP9 has since been detected in human adipose tissue [ 28 , 29 , 30 ] and in 3T3-L1 adipocytes [ 31 ], respectively. Moreover, AQP3 mRNA levels are higher in 3T3-L1 adipocytes as compared to preadipocytes, while AQP9 mRNA levels are similar [ 31 ]. In addition, obesity has been associated with increased AQP3 and AQP9 expression and decreased AQP7 expression in human subcutaneous adipose tissue [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, as shown in Fig. 4 d, we used miRDB database and Venn analysis software to screen out 16 upregulated genes, including RAR-related orphan receptor alpha (RORα), TROVE domain family, member 2(Trove2), Collagen, type IV, alpha 3 (Goodpasture antigen) binding protein (Col4A3Bp), C2 domain-containing protein 2 (C2Cd2), Zinc finger protein 606 (ZFP606), suppressor of cytokine signaling (SOCS4), Receptor-type tyrosine-protein phosphatase eta (PTPRJ), G proteincoupled receptor 158 (GPR158), 111005, Brain abundant membrane attached signal protein 1(BASP1), sparc/ osteonectin, cwcv and kazal-like domains proteoglycan 3(SPOCK3), Glycosyltransferase-like domain-containing protein 1(GTDC1), Aquaporin11(Aqp11), transmembrane emp24 protein transport domain containing 5 (TMED5), G protein-coupled receptor22(GPR22), and Synaptotagmin-4 (Syt4), which were closely associated with inflammatory diseases according to previous literatures [34][35][36][37]. To further investigate the putative target of miR-7, we verified the expression levels of these 16 predicted target genes, respectively.…”
Section: Rorα Is a Novel Direct Target Of Mir-7 In Bti Modelmentioning
confidence: 99%